2011
DOI: 10.5194/nhess-11-513-2011
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric perturbations in possible association with the 2010 Haiti earthquake, as based on medium-distance subionospheric VLF propagation data

Abstract: Abstract. Ionospheric perturbations in possible associationwith the 2010 Haiti earthquake occurred on 12 January 2010 (with a magnitude of 7.0 and depth of 10 km) are investigated on the basis of subionospheric propagation data from the NAA transmitter on the east coast of the USA to a VLF receiving station in Peru. The local nighttime VLF amplitude data are extensively investigated during the period from the beginning of October 2009 to the end of March 2010, in which the trend (nighttime average amplitude), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The third parameter, NF is defined by the area of dA(t) < 0 integrated over the whole nighttime. In fact, this method has been applied extensively to identify the ionospheric anomaly related to the seismic activity as significant decrease in Trend associated with increase in both Dispersion and NF (e.g., Hayakawa et al, 2011).…”
Section: Data Pre-processing Methodologymentioning
confidence: 99%
“…The third parameter, NF is defined by the area of dA(t) < 0 integrated over the whole nighttime. In fact, this method has been applied extensively to identify the ionospheric anomaly related to the seismic activity as significant decrease in Trend associated with increase in both Dispersion and NF (e.g., Hayakawa et al, 2011).…”
Section: Data Pre-processing Methodologymentioning
confidence: 99%
“…Hasbi et al (2011) investigated the ionospheric variations before four earthquakes with M ≥ 7.9 that occurred during [2004][2005][2006][2007] in Sumatra using GPS and CHAMP data, and the result shows the occurrence of positive and negative anomalies detected within a few hours to 6 days before the earthquakes. Hayakawa et al (2008Hayakawa et al ( , 2011 analyzed subionospheric VLF propagation data and found perturbations before the 2007 Niigata Chuetsu-Oki 6.8 earthquake and the 2010 Haiti 7.0 earthquake with an abnormal radius up to several kilometers. On 9 May, just 3 days before the Wenchuan 8.0 earthquake, TEC and foF2 of GPS observations, electron density and ion density of DEMETER satellite were subjected to an abrupt increase or decrease with amplitude being up to 40 %-80 %.…”
Section: Introductionmentioning
confidence: 99%
“…Events that are not in close proximity to the receiver, can at most produce disturbances in stations that are in the same bearing as the seismic event in question, as it has been shown in previous studies [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], concerning a variety of methods and disturbances. In the case of this particular seismic event, which took place near the receiver, a disturbance is evident across the signals of all the stations and especially the VLF stations and provides a clear pattern to pinpoint and detect the precursor phenomena of a seismic event in the area close to the receiving antenna.…”
Section: Resultsmentioning
confidence: 64%
“…Agreat amount of research in the last twenty years by means of ground-based experiments [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], spaceborn studies [18], [19], [20] and combined space-born and ground-based studies [21], [22] as well, indicate the existence of pre-, co-and post-earthquake ionospheric perturbations at all ionospheric layer levels (D, E and F layers).…”
Section: Introductionmentioning
confidence: 99%